Rethinking social movements after '68 : selves and solidarities in West Germany and beyond - Davis, Belinda J. 1959- HerausgeberIn; Brühöfener, Friederike 19XX- HerausgeberIn; Milder, Stephen HerausgeberIn (Protest, culture and society, 2022)
The year 1968 has widely been viewed as the only major watershed moment during the latter half of the twentieth century. Rethinking Social Movements after ’68 takes on this conventional approach, exploring the spaces, practices, organization, ideas and agendas of numerous activists and movements across the 1970s and 1980s. From the Maoist Communist League to the women’s movement, youth center movement, and gay liberation movement, established and emerging scholars across Europe and North America shed new light on the development of modern European popular politics and social change.